User motivation and sustained participation in walking donation as a virtual corporate social responsibility co-creation project - Wei Li; Tingting Wang; Doris Chenguang Wu (Humanities & Social Sciences Communications)
Abstract As leisure sports are becoming important for modern people, social platforms have initiated “Walking Donation”, which is one of the virtual corporate social responsibility (VCSR) co-creation projects utilizing users’ exercise data. Users’ continuous participation plays an essential role in the sustainable development of co-creation projects. This study develops a theoretical framework to investigate how user participation motivations are linked to continuous participation intention, with project design satisfaction acting as a mediating factor and policy support perception serving as a moderating influence. This framework is further tested using a structural equation model and a hierarchical regression with 506 respondents. The results show that user participation motivations, including personal social responsibility, physical and mental health, and online persona, have positive impacts on user’s continuous participation intention. The study also uncovers that user satisfaction with two co-creation project designs, namely incentive design and esthetics design, is identified to mediate these relationships. Furthermore, policy support perception is found to moderate these relationships. From the perspective of leisure sports, this research extends the VCSR co-creation research by incorporating individual users, social platforms, philanthropic organizations and the governments into one framework for examination. The findings provide both industries and governments with potential strategies for enhancing sustained participation in VCSR co-creation initiatives.